TGF-1 mRNA, AFP-L3, and Annexin II in the Early and Late Detection of Hepatocellular Carcinoma: The Diagnostic Value - Youssef , Eman; El-Khouly, Nashwa; Elzahrani , Yahia Abdullah; Tash , Rehab M. E.; Khalifa, Eman A.; Bayoumy , Eman S. M.; Khalil, Mona; Edreis, Awatif E.; Mohamed, Fatma Saffeyeldin; Abdou, Aml E.; Seliem, Nora; Sofy, Mahmoud; et al. (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Alpha-fetoprotein (AFP) is the recommended screening biomarker for hepatocellular carcinoma (HCC), despite its drawbacks: AFP-negative HCC, poor specificity, and sensitivity. As a result, new HCC-sensitive and specific biomarkers are urgently needed. AIM: This study aimed to determine the diagnostic value of transforming growth factor (TGF)-β1 mRNA and Annexin II in the early detection and follow-up of HCC. PATIENT AND METHODS: This research involved 75 HCC patients (30 early and 45 late) and 75 liver cirrhosis (LC) patients (all patients have HCV), and 75 healthy individuals as controls. Reverse transcription polymerase chain reaction measured TGF-β1 mRNA. Enzyme-linked immunosorbent assay ELISA measured Annexin II, AFP-L3, and AFP. RESULTS: Annexin II was a biomarker with a significant difference between the LC and early HCC groups. TGF-β1 mRNA showed a significant difference when the LC group was compared to the control group and the late HCC group. CONCLUSION: Annexin II has better sensitivity and specificity for early HCC detection than AFP, and TGF-β1 mRNA can be used for the assessment of the degree of HCC, and TGF-1 signaling inhibitors may be a possible new treatment choice for HCC.